2004
DOI: 10.1148/radiol.2331030660
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Volume in Pharyngolaryngeal Squamous Cell Carcinoma: Comparison at CT, MR Imaging, and FDG PET and Validation with Surgical Specimen

Abstract: Compared with GTVs at CT and MR imaging, GTVs at FDG PET were smaller. In nine patients for whom a surgical specimen was available, PET was found to be the most accurate modality. However, no modality managed to depict superficial tumor extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
384
3
15

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 622 publications
(421 citation statements)
references
References 18 publications
19
384
3
15
Order By: Relevance
“…Because of the good correlation between the MTV and the GTV assessed by other imaging tools such as CT [11,12], we can expected that MTV may be another important factor to be considered in the management of HNSCC. A study to compare CT, MRI, and FDG PET for delineation of tumor volume in pharyngolaryngeal squamous cell carcinoma with the results validated by surgical specimen indicated that FDG PET was the most accurate modality for measuring tumor volume [36].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the good correlation between the MTV and the GTV assessed by other imaging tools such as CT [11,12], we can expected that MTV may be another important factor to be considered in the management of HNSCC. A study to compare CT, MRI, and FDG PET for delineation of tumor volume in pharyngolaryngeal squamous cell carcinoma with the results validated by surgical specimen indicated that FDG PET was the most accurate modality for measuring tumor volume [36].…”
Section: Discussionmentioning
confidence: 99%
“…Gradientbased methods rely on a model that determines the appropriate threshold of activity on the basis of the signal-to-background ratio [59]. This method was shown to be accurate for segmenting PET images in a study of pharyngeal-laryngeal tumors [60].…”
Section: Source / Background Algorithmsmentioning
confidence: 99%
“…Careful comparison of FDG-PET, MRI and CT scans with the histopathology of resected tumour specimens shows that none of these three imaging modalities is [60]. However FDG-PET may be the most accurate of the three for the detection of head and neck cancer [106].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Accurate PET/CT image alignment is essential for precise delineation and localization of the gross target volume (GTV). ( 7 , 8 ) In addition, magnetic resonance imaging (MRI) provides high soft tissue contrast and is often required for target delineation, ( 9 , 10 ) especially for stereotactic radiosurgery (SRS) procedures. Different MRI sequences, such as T1, T2 or fluid attenuated inversion recovery (FLAIR), enhance different aspects of soft tissue, helping to distinguish the GTV from local edema.…”
Section: Introductionmentioning
confidence: 99%